Approaches to integrate land-use and transport planning: Analysing the political dimension of integrative planning - Meike Levin-Keitel; Irina Kim Reeker (Raumforschung und Raumordnung / Spatial Research and Planning, 2021)
Spatial structures influence our travel distances between home, work, shopping or leisure and determine our mobility behaviour to a considerable extent. Although they are not the only determinants of our daily travel distances and times or our choice of different means of transport, the interrelations between spatial structures and mobility behaviour is often considered in the literature. Overall, the integration of land use and transportation planning is a key aspect in the shift towards sustainable mobility. This integrated planning approach is characterised, for instance, by increased cross-sector interaction, softened institutionalised boundaries between the two sectors of land-use and transportation planning, and shared cross-sector goals. In its implementation, however, this frequently postulated call for integration remains unclear. This paper uses the conceptual framework of the three dimensions of policy, polity and politics to empirically capture this integration in its various aspects. The two German cities of Dortmund and Hannover serve as case studies. The findings suggest that informal interaction (politics) between the two sectors is a necessary precondition for integration, while political will and cross-sectorally shared strategic goals (policy) are required to actually set the process of integration in motion. Ultimately, an approach is fully integrated when institutional structures (polity) are adapted in the sense of hierarchical coordination and the extensive elimination of sectoral boundaries. – – Räumliche Strukturen beeinflussen, welche Wege wir zwischen Wohnort, Arbeitsort, Einkaufsmöglichkeiten oder Freizeitvergnügen zurücklegen und bestimmen in erheblichem Maße unser Mobilitätsverhalten. Zwar sind sie nicht allein bestimmend über unsere täglichen Wegstrecken und Weglängen sowie unsere Wahl der Verkehrsmittel, doch wird der Zusammenhang zwischen räumlichen Strukturen und dem Mobilitätsverhalten in der Literatur stets aufgenommen. Schlussfolgernd ist die Integration von Flächennutzungs- und Verkehrsplanung ein zentraler Aspekt im Wandel hin zu einer nachhaltigen Mobilität. Dieser integrierte Planungsansatz zeichnet sich beispielsweise durch verstärkte sektorübergreifende Interaktion, aufgeweichte institutionalisierte Grenzen zwischen den beiden Sektoren der Flächennutzungs- und Verkehrsplanung sowie gemeinsame sektorübergreifende Ziele aus. In ihrer Umsetzung bleibt diese häufig postulierte Forderung nach Integration jedoch unklar. Dieser Beitrag nutzt den konzeptionellen Rahmen der drei Politikdimensionen Policy, Polity und Politics, um diese Integration in ihren verschiedenen Aspekten auch empirisch zu erfassen. Als Fallstudien dienen die beiden deutschen Städte Dortmund und Hannover. Ergebnis ist, dass informelle Interaktion (Politics) zwischen beiden Sektoren eine notwendige Voraussetzung für Integration ist, während politischer Wille und sektorübergreifend geteilte strategische Ziele (Policy) erforderlich sind, um den Prozess der Integration tatsächlich in Gang zu setzen. Letztlich ist ein Ansatz dann vollständig integriert, wenn institutionelle Strukturen (Polity) im Sinne einer hierarchischen Koordination und einer weitgehenden Aufhebung sektoraler Grenzen angepasst werden.
Keywords: 710; Integrated planning; transport planning; conceptualisation of integration; policy; politics; polity; Dortmund; Hannover; Integrierte Planung; Verkehrsplanung; Konzeptualisierung von Integration